Effect of Chinese Medicine on the Biological Behavior and Magnetic Resonance Imaging of Bladder Cancer - Hengxin Qi (Hindawi Limited, 2021)
Objective. This study aimed to investigate the effects of traditional Chinese medicine (TCM) on biological behavior and magnetic resonance imaging and recurrence rate of patients with bladder cancer. Method. Forty-seven postoperative bladder cancer patients treated in our hospital who met the criteria were selected and randomly divided into the TCM treatment group (observation group) and the group without TCM treatment (control group). In the TCM treatment group, the prescription was slightly adjusted according to the different symptoms, and the main prescription remained unchanged. According to the treatment plan, patients continued to undergo bladder irrigation chemotherapy plus TCM treatment, while the control group was only treated with bladder irrigation chemotherapy. The number of patients with recurrence at 3 and 6 months and 1 year, the effects on patients’ clinical symptoms, and quality of life were observed, respectively. The changes in MRI images, blood routine, immune function, and leukocyte level and other related indexes before and after treatment were compared between the two groups. Results. After the patients in the observation group were treated with traditional Chinese medicine, the patients’ quality of life significantly improved. The patients’ CD3+, CD4+, and CD4+/CD8+ indexes were significantly higher than those of the control group. The levels of Hb and PLT of the patients in the observation group were significantly lower than those of the patients in the control group. Patients in the observation group had higher leukocyte levels and a lower recurrence rate than patients in the control group. Conclusion. TCM with chemotherapy drugs can effectively improve patients’ immune function, increase the level of T-lymphocyte subpopulation, and improve bone marrow hematopoietic function, which has a significant effect on the prevention and treatment of bladder cancer recurrence after surgery.